2017
DOI: 10.1099/jmmcr.0.005096
|View full text |Cite
|
Sign up to set email alerts
|

A case of Vibrio vulnificus infection complicated with fulminant purpura: gene and biotype analysis of the pathogen

Abstract: Introduction. Vibrio vulnificus (V. vulnificus) causes a severe infection that develops in the compromised host. Its pathophysiology is classified into three types: (1) primary septicaemia, (2) gastrointestinal illness pattern and (3) wound infection pattern. Of these, primary septicaemia is critical. V. vulnificus can be classified into three biotypes and two genotypes and its pathogenicity is type-dependent. Case presentation. A 47-year-old man presented to a local hospital with chief complaints of fever, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…Genotyping analysis of V vulnificus has shown that strains with low pathogenicity can cause primary septicemia in humans. 7 Our case reinforces the need to quickly recognize V vulnificus as a rare underlying cause of PF and administer the appropriate treatment.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Genotyping analysis of V vulnificus has shown that strains with low pathogenicity can cause primary septicemia in humans. 7 Our case reinforces the need to quickly recognize V vulnificus as a rare underlying cause of PF and administer the appropriate treatment.…”
supporting
confidence: 73%
“…In one previously reported case, the patient was otherwise healthy and managed to recover following antibiotic therapy and wound debridement, 6 whereas in another case the patient had undiagnosed liver cirrhosis and died from the infection. 6,7 In the latter case, the patient presented to the emergency department in a coma. Our patient did not have the clinical signs of sepsis upon initial presentation to the emergency department.…”
mentioning
confidence: 99%
“…A further biotype (biotype 3) was discovered in 1996 after an outbreak of V. vulnificus wound infections in an Israeli fish market, and was later found to be a hybrid of biotypes 1 and 2 (Bisharat et al ., ). To date biotype 3 strains have been geographically restricted to Israel, with the exception of a recent infection reported in Japan (Hori et al ., ). In addition, cells of all three biotypes are comprised of two genotypes (based on the vcg gene), a clinical (‘C’) genotype, responsible for virtually all septicemia cases, and an environmental (‘E’) genotype, which causes virtually all of the wound infections (Oliver and Baker‐Austin, ).…”
Section: The Hunt For Virulence Markersmentioning
confidence: 97%
“…Strong evidence suggests that climate change is influencing outbreaks and changing the epidemiology of Vibrio infections on a worldwide scale and will increase the spread of aquatic Vibrio pathogens, with detrimental effects on human and animal health ( 32 , 33 , 34 ). Although the V. vulnificus biotype 3 strain was originally isolated from outbreaks associated with tilapia farming in Israel ( 8 ), a biotype 3–associated case with primary septicemia was also reported in Japan ( 35 ), indicating that the habitat of the V. vulnificus biotype 3 has extended to East Asia and might spread worldwide in the future. Our study providing new insights into the mechanisms by which opportunistic bacteria make evolutionary trade-offs to increase their fitness in the environmental reservoir should expand our understanding of the regulation of virulence across a wide range of emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%